Women, transition, and change : a study of the impact of conflict and displacement on women in traditional Tamil society. - Institute of Agriculture and Women in Development (Colombo, Sri Lanka); Friedrich-Ebert-Stiftung (Sri Lanka) (Colombo : Institute of Agriculture and Women in Development, Friedrich Ebert Stiftung, and Gala Academic Press, 1995)
With special reference to Tamil society in Sri Lanka.
Keywords: Women -- Sri Lanka -- Social conditions; Women, Tamil -- Sri Lanka; Sri Lanka -- Ethnic relations